Standardization of endoscopic resection for colorectal tumors larger than 10 mm in diameter. (20th April 2017) - Oka, Shiro; Uraoka, Toshio; Tamai, Naoto; Ikematsu, Hiroaki; Chino, Akiko; Okamoto, Koichi; Takeuchi, Yoji; Imai, Kenichiro; Ohata, Ken; Shiga, Hisashi; Raftopoulos, Spiro; Lee, Bo‐in; et al.
Abstract : Currently, several endoscopic resection (ER) methods for colorectal tumors are available, including polypectomy, conventional endoscopic mucosal resection (EMR), endoscopic submucosal dissection (ESD), and modified ER. In the present review, we mainly focus on the current status of ER for colorectal tumors as well as the report from the Endoscopic Forum Japan (EFJ) 2016, which was held in Tokyo in August 2016. The proposed ER methods for colorectal tumors larger than 10 mm in diameter are as follows. (i) Pedunculated‐type tumor is an indication for polypectomy, regardless of size. (ii) Non‐pedunculated‐type tumor larger than 20 mm in diameter is an indication for ESD in which en bloc resection using conventional EMR is difficult or impossible. (iii) Non‐pedunculated‐type tumor from 10 mm to 20 mm in diameter is an indication for conventional EMR. However, ESD or modified ER methods are acceptable according to the procedure and the condition of the tumor.